Chronicle of the Roman Emperors : The Reign-by-Reign Record of the Rulers of Imperial Rome - Scarre, Chris (New York Thames and Hudson, 2000)
Chronicle of the Roman Emperors is the first book to focus on the succession of rulers of imperial Rome, using timelines and other visual aids throughout. Now no one need be in any doubt as to who built the Colosseum or when Rome was sacked by the Goths: the Chronicle provides the answers, quickly and authoritatively. This is only one aspect, however, of the book's value. The biographical portraits of the 56 principal emperors from Augustus to Constantine, together with a concluding section on the later emperors, build into a highly readable single-volume history of imperial Rome. Colorful contemporary judgments by writers such as Suetonius and Tacitus are balanced by judicious character assessments made in the light of modern research. The famous and the infamous - Caligula and Claudius, Trajan and Caracalla - receive their due, while lesser names emerge clearly from the shadows for the first time.
Include Illustrations, Bibliography and Index.
The Reign-by-Reign Record of the Rulers of Imperial Rome.
Keywords: Rome (Empire) -- Emperors -- Kings and rulers